STRATEGI PEMASARAN PT. SUKSES INTERNASIONAL TOUR & TRAVEL DALAM MENGHADAPI PERSAINGAN BISNIS UMRAH DI BUKITTINGGI - Tetti Maharani; Khadijah Nurani (CV. Adiba Aisha Amira, 2024)
Marketing strategy is a fundamental tool designed to achieve company goals by developing sustainable competitive advantages to enter the market and serve predetermined target markets. The increasing public interest in carrying out the Umrah has resulted in Umrah travel popping up in Bukittinggi. Therefore, PT. Successful International Tour & Travel needs to develop a good marketing strategy in order to face competition in the Umrah business in Bukittinggi. The purpose of this research is to find out how the marketing strategy of PT. Success of International Tour & Travel in Facing Umrah Business Competition in Bukittinggi. This type of research is qualitative research carried out at PT. Success of International Tour & Travel Bukittinggi through observation, interviews and documentation regarding research objects. The data analysis technique used in this research is SWOT analysis. The results of research conducted at PT. Bukittinggi Tour & Travel International Success: Marketing Strategy Development carried out by PT. International Tour & Travel's success in facing competition in the Umrah business in Bukittinggi is using the SO strategy, namely (1) Providing varied packages (2) Oflering various prices according to facilities (3) Providing satisfactory service (4) Providing quality human resources (5) Providing complete facilities and infrastructure.